TEORI EVOLUSI MANUSIA DALAM PERSPEKTIF AL-QUR’AN - Aas Siti Sholichah (el-'Umdah, 2019)
This paper will analyze the theory of human evolution that developed in the West and the theory of human evolution that is explained in the Qur'an with the interpretation approach. The method used in this paper is to use qualitative methods derived from sharing books relating to the above problems. The approach to the interpretation method of the Qur'an uses the thematic method, because this method can study contemporary problems. The theory of evolution began to be studied and debated in the 6th century BC, beginning with the Greek philosopher Anaximander, Empedocles, Lucretius, the same opinion was expressed by Arab biologist Al Jahiz, Persian philosopher Ibn Miskawaih, Ikhwan As-Shafa, and Chinese philosopher Zhuangzi. Furthermore, the theory of evolution was published by a British scientist named Charles Darwin, the results of his research on evolution, especially human evolution, explained that the theory of evolution was not created by God but stood alone. This opinion caused debate among scientists and religious leaders especially Islam was rejected because it contradicted the Qur'an.